(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This paper focuses on the study of acoustic propagation of internal gravity waves which generates small scale variations through propagation and hence can obtain transmission co-efficients using N2 buoyancy frequency variation of a compressible stratified fluid for a small regions. We have also analysed the results using the asymptotic expansions for large compressible limits. The reduction of the transmission in the N2-barrier region for the density layers sandwiched along with acoustic waves is obtained through graphs for different density barrier regions. The dispersion characteristics shows the contours of the transmission in the wave number plane. The curves for ! < N0 are hyperbolic, representing internal gravity waves as these become the dispersion waves for an incompressible fluid and the curve with ! > N0 are ellipsoids which represent the acoustic gravity or infrasonic waves for the cut off frequency